2018
DOI: 10.1111/tan.13358
|View full text |Cite
|
Sign up to set email alerts
|

HLA common and well‐documented alleles in China

Abstract: The American Society for Histocompatibility and Immunogenetics HLA common and well‐documented (CWD) catalog, CWD 2.0.0 catalog and European Federation for Immunogenetics (EFI) CWD catalog have been published, which are useful for improving the accuracy of HLA genotyping in laboratories. Here, we studied the Chinese HLA CWD catalog. A total of 812 211 unrelated volunteer donors from the China Marrow Donor Program (CMDP) were analyzed. Six hundred seventy‐six alleles at the HLA‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 loci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
82
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 24 publications
(35 reference statements)
0
82
1
1
Order By: Relevance
“…According to the latest version of the IPD‐IMGT/HLA Database release 3.34 version (2018‐10), a total of 20 088 alleles for HLA loci have been found in populations from around the world, including 4374 alleles for HLA‐C locus. It was reported that 125 common and well documented (CWD) HLA‐C alleles were found in the Chinese population from the database of the China Marrow Donor Program (CMDP) . In this report, we describe the identification of the new allele HLA‐C*03:365 , which has been found in a Chinese bone marrow donor.…”
mentioning
confidence: 99%
“…According to the latest version of the IPD‐IMGT/HLA Database release 3.34 version (2018‐10), a total of 20 088 alleles for HLA loci have been found in populations from around the world, including 4374 alleles for HLA‐C locus. It was reported that 125 common and well documented (CWD) HLA‐C alleles were found in the Chinese population from the database of the China Marrow Donor Program (CMDP) . In this report, we describe the identification of the new allele HLA‐C*03:365 , which has been found in a Chinese bone marrow donor.…”
mentioning
confidence: 99%
“…It was reported that the top three most frequent alleles in HLA‐B locus were HLA‐B*40:01 , B*46:01 and B*58:01 with the frequency of 14.08%, 12.20% and 8.50%, respectively in the Zhejiang Han population, China . According to the data of the Chinese Marrow Donor Program Database (CMDP), the HLA‐B*40:01 allele is common in the Chinese Han population . Here, we describe a novel allele HLA‐B*40:357 , which differs from HLA‐B*40:01 by one nucleotide substitution.…”
mentioning
confidence: 99%
“…The HLA molecule shows particularly high levels of polymorphism, and the distributions of HLA alleles and haplotypes are varied among different populations. According to the HLA common and well‐documented alleles in China, HLA‐B*46:01 is a common allele in the Chinese population. It was reported that the frequency of the HLA‐B*46:01 allele was 11.87% in the Zhejiang Han population, China .…”
mentioning
confidence: 99%